A Hybrid method of SWARA and ARAS for ranking of supplier: A case study at PT.Adi Satria Abadi (PT.ASA) - Ristono, Agus; Wahyuningsih, Tri; Putro, Gunawan Madyono (OPSI, 2024)
The development of a suggested model for rating suppliers is the goal of this research. In this study, suppliers are rated and ranked using Additive Ratio Assessment (ARAS) and Stepwise Weight Assessment Ratio Analysis (SWARA). The suggested approach incorporates both objective and subjective criteria while applying Delphi to a subset of the criteria. In order to test the proposed model in a leather company for actual use, a case study is provided. The model is able to capture all objective and arbitrary criteria in the dynamics of the group of decision-makers when rating suppliers. To help in decision-making, this proposed model includes criteria selection. Because the results of the ranking of suppliers will depend on how accurately the criteria are chosen. The suggested approach produces a workable resolution because it is not sensitive to changes in the parameters